Inflammation leads through PGE/EP3 signaling to HDAC5/MEF2‐dependent transcription in cardiac myocytes - András D Tóth; Richard Schell; Magdolna Lévay; Christiane Vettel; Philipp Theis; Clemens Haslinger; Felix Alban; Stefanie Werhahn; Lina Frischbier; Jutta Krebs‐Haupenthal; Dominique Thomas; Hermann‐Josef Gröne; et al. (EMBO Molecular Medicine, 2018)
Abstract The myocyte enhancer factor 2 (MEF2) regulates transcription in cardiac myocytes and adverse remodeling of adult hearts. Activators of G protein‐coupled receptors (GPCRs) have been reported to activate MEF2, but a comprehensive analysis of GPCR activators that regulate MEF2 has to our knowledge not been performed. Here, we tested several GPCR agonists regarding their ability to activate a MEF2 reporter in neonatal rat ventricular myocytes. The inflammatory mediator prostaglandin E2 (PGE2) strongly activated MEF2. Using pharmacological and protein‐based inhibitors, we demonstrated that PGE2 regulates MEF2 via the EP3 receptor, the βγ subunit of Gi/o protein and two concomitantly activated downstream pathways. The first consists of Tiam1, Rac1, and its effector p21‐activated kinase 2, the second of protein kinase D. Both pathways converge on and inactivate histone deacetylase 5 (HDAC5) and thereby de‐repress MEF2. In vivo, endotoxemia in MEF2‐reporter mice induced upregulation of PGE2 and MEF2 activation. Our findings provide an unexpected new link between inflammation and cardiac remodeling by de‐repression of MEF2 through HDAC5 inactivation, which has potential implications for new strategies to treat inflammatory cardiomyopathies.